IMPROVING CRITICAL THINKING ABILITY AND BIOLOGY LEARNING OUTCOMES IN SENIOR HIGH SCHOOL WITH THE SCIENCE TECHNOLOGY AND SOCIETY APPROACH WITH THE ASSISTANCE OF E-LKPD - Yuniastuti, Nanik (Universitas Negeri Yogyakarta, 2023)
The aim of this research is to explain the application of the STS (Science, Technology, and Society) approach with the assistance of E-LKPD to improve critical thinking skills and Biology learning outcomes for class XI PMIIA5 students on immune system material at SMA Negeri 2 Yogyakarta in the 2020/2021 academic year. The type of research carried out is Classroom Action Research (CAR) which follows the model of Stephen Kemmis and Robin McTaggart, through the stages of planning, action, observation, and reflection (reflecting). The approach of Science, Technology, and Society Assisted by E-LKPD is carried out by following stages 1) invitation; 2) exploration (exploration); 3) explanations and solutions (proposing explanations and solutions); and 4) taking action. The results of the action showed that all indicators of critical thinking skills increased in cycle 2. The average indicator of critical thinking skills increased by 0.14 points from 2.89 to 3.03 in cycle 2. The indicator of rejecting incorrect and irrelevant information increased from 3.14 to 3.25 in cycle 2. The indicator of detecting and correcting conceptual errors increased from 2.77 to 2.83 in cycle 2. The indicator of seeking new solutions increased from 2.64 to 2.96 in cycle 2. While the indicator made a decision or conclusion after collecting the facts increased from 3.01 to 3.08 in cycle 2. Learning outcomes data showed that the average value of student evaluation increased by 12.37 points from 62.8 to 75.17 in cycle 2. The percentage of class completeness increased by 44 points from 33% to 77% in cycle 2. While the percentage of class incompleteness decreased by 44 points from 67% to 23% in cycle 2. In general, the average value of all poster assessment indicators increased by 1.23 points from 94.7 7 becomes 96.00 in cycle 2.